Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

George was solving the equation (2x-1)(x+3)=4 and he got the solution x=1/2 and x=-3. Jeffrey came along and said, "You made a big mistake! You set each factor equal to zero, but it's not equal to zero, it's equal to 4. So you have to set each factor equal to 4 and then solve." Who is correct? Show George and Jeffrey how to solve this equation. To be sure that you are correct, check your solutions. ​

Sagot :

The solution to the system of equation is -7/2 and 1

Solving linear equation

An algebraic expression is an expression which is made up of variables and constants, along with algebraic operations such as the addition, subtraction, division and multiplication.

Given the quadratic equation below;

(2x-1)(x+3)=4

Expand

2x^2+6x-x-3 = 4

2x^2+5x-3-4=0

2x^2+5x-7=0

2x^2-2x+7x-7=0

2x(x-1)+7(x-1) = 0

2x+7 = 0 and x - 1 = 0

x = -7/2 and x = 1

Hence the solution to the system of equation is -7/2 and 1

Learn more on system of equation here:https://brainly.com/question/14323743

#SPJ1